More bears, less bears: Inuit and scientific perceptions of polar bear populations on the west coast of Hudson Bay - Tyrrell, Martina (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractInuit and scientific perceptions of polar bear populations are grounded in different epistemologies, relationships and interactions with polar bears. In many communities, the presence of polar bear hunting quotas has led to both external and internal conflicts. Inuit throughout Nunavut are seeing more polar bears in close proximity to their communities. Scientists argue that the increase in bear-human encounters is due to rapid environmental change, leading to a decrease, rather than an increase, in polar bear numbers. These opposing perceptions result in confrontation regarding the hunting and protection of bears. Within communities, ethical, social and economic conflicts arise with regard to the enactment of the quota system due to differing views on the allocation of the quota, the existence of a sport hunt, and the morality of such an intense focus on polar bears. One such community is Arviat, on the west coast of Hudson Bay. The people of Arviat feel particularly vulnerable to the year-round presence of polar bears in and near their community. The inclusion of women in the hunt and the cost of undertaking a bear hunt, lead to discussion and mixed feelings about the open hunting season each year. While the situation in Arviat is in some ways unique, it also serves as an example of the questions and concerns facing Inuit across the Canadian Arctic as they increasingly have to deal with polar bears on their doorstep.